2007
DOI: 10.1016/j.jtcvs.2007.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the radial artery anastomosed to the internal thoracic artery as a composite straight graft

Abstract: These results suggest that a composite straight radial and internal thoracic artery graft without a change in shear stress behaves like an extended arterial graft, with remodeling and vasoreactive capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Fukui, Calafiore, and Tatoulis consider, based on angiographic results obtained at 12 months, 17.5 months, and 41,5 months postoperatively, that there are no differences in patency rates and prognosis between free ITAs with composite anastomosis and in situ ITAs on one hand and between pedicled and skeletonised grafts on the other hand (1921). In our study, in situ RITA was used exclusively for the RCA territory and free ITAs as composite grafts for the anterolateral or CX territory, thus introducing another variable in the equation, the coronary territory.…”
Section: Discussionmentioning
confidence: 99%
“…Fukui, Calafiore, and Tatoulis consider, based on angiographic results obtained at 12 months, 17.5 months, and 41,5 months postoperatively, that there are no differences in patency rates and prognosis between free ITAs with composite anastomosis and in situ ITAs on one hand and between pedicled and skeletonised grafts on the other hand (1921). In our study, in situ RITA was used exclusively for the RCA territory and free ITAs as composite grafts for the anterolateral or CX territory, thus introducing another variable in the equation, the coronary territory.…”
Section: Discussionmentioning
confidence: 99%
“…NO released from endothelium plays a crucial role in the remodeling of vascular diameter depending on shear stress [ 18 ]. Fukui and colleagues [ 19 ] reported that a non-skeletonized RA graft adjusts its caliber to suit the flow requirement, which eventually normalizes shear stress at the endothelial interface and allows the conduit to deliver an appropriate flow. Low shear stress induces the attachment of endothelial cells and leukocytes, resulting in thrombus, intimal hyperplasia, and subsequent graft failure [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early and late results of endto-end (tandem) and end-to-side (T configuration) composite IMA grafts were reported by Tector et al, [3], with similar outcomes for both. Composite tandem arterial grafts using the radial artery with inflow from the in situ right IMA have also been described with excellent short-term results [4,5]. This might seem to be an extravagant use of arterial conduit for a benefit not yet determined but it substantially increases the versatility of arterial grafting in coronary surgery.…”
Section: Introductionmentioning
confidence: 99%